EFFECT OF CADMIUM ON SOME BIOCHEMICAL MECHANISM IN THE SACCHAROMYCES CEREVISIAE - Canakci-Gulengul, Songul; Yildiz, Tugba; Yilmaz, Okkes; Ozsahin, Ayse Dilek (Parlar Scientific Publications (P S P), 2017)
Toxic heavy metals in industrial waste are caused environmental pollution. Microorganisms are a powerful heavy metal remover, and all yeast cells possess the power to accumulate heavy metals. In this study, having toxic properties of cadmium chloride (CdCl2) was added to the culture medium of the bread yeast cells (S. cerevisiae) at different concentrations and its effects was investigated on some biochemical properties. According to experimental results, depending on cadmium chloride (CdCl2) concentration lipid peroxidation, glutathione and protein values were increased (p<0.001). However, a-tocopherol, ergosterols, vitamin K-1, stigmasterol and beta-sitosterol levels decreased in the groups treated with CdCl2 (p<0.05, p<0.001). Although, the fatty acids such as palmitic (16:0), palmitoleic (16:1, n 7), stearic (18:0), oleic (18:1, n 9) and linoleic (18:2, n 6) levels in 2-4 mu mol treated CdCl2 groups were slightly decreased (p<0.05), the same fatty acid levels were increased in 8 mu mol treated CdCl2 group (p<0.01). As a result, it was observed that depending on the cadmium chloride concentration against increased oxidative stress, the baker's yeast S. cerevisiae are responded, increasing of the synthesis glutathione, protein and some fatty acids in the cells.
Keywords: S. cerevisiae; Cadmium toxicity; Glutathione (GSH); Lipid peroxidation (MDA); Fatty acids